2000
DOI: 10.3348/jkrs.2000.42.6.897
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Evaluation of Intra-arterial Infusion of Urokinase for Acute Ischemic Stroke

Abstract: Acute occlusion of the intracranial artery probably causes sudden severe neurological ischemic change, and the prognosis is poor (1, 2). In patients with acute ischemic stroke, intra-arterial infusion of urokinase has To evaluate the results of intra-arterial urokinase thrombolysis in cases of acute ischemic stroke and to define the factors affecting prognosis.Forty-eight patients with angiographically proven occlusion of the intracranial arteries were treated with local intra-arterial infusion of urokinase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…However, in Korea, this procedure has yielded variable results (9-11). A combination of microcatheter techniques with their improved performance has increased the effectiveness and safety of IA thrombolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Korea, this procedure has yielded variable results (9-11). A combination of microcatheter techniques with their improved performance has increased the effectiveness and safety of IA thrombolysis.…”
mentioning
confidence: 99%
“…With the first successful use of local intra-arterial (IA) thrombolysis for vertebrobasilar disease ( 1 ), many studies have shown that IA application of thrombolytics can successfully treat hyperacute ischemic strokes ( 2 - 8 ). However, in Korea, this procedure has yielded variable results ( 9 - 11 ). A combination of microcatheter techniques with their improved performance has increased the effectiveness and safety of IA thrombolysis.…”
mentioning
confidence: 99%